2009
DOI: 10.18388/abp.2009_2521
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype modifiers of spinal muscular atrophy: the number of SMN2 gene copies, deletion in the NAIP gene and probably gender influence the course of the disease.

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder caused by mutations of the SMN1 gene. It is characterized by significant phenotype variability. In this study, we analyzed possible phenotype modifiers of the disease - the size of the deletion in the SMA region, the number of SMN2 gene copies, as well as the effect of gender. Among the factors analyzed, two seem to influence the SMA phenotype: the number of SMN2 gene copies and a deletion in the NAIP gene. A higher number of SMN2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 30 publications
7
27
2
Order By: Relevance
“…In our studied population, all patients with three SMN2 copies presented with milder types II and III phenotypes whereas all severe Type I carried two copies. Our data are in concordance with the reported inverse relationship between SMN2 copy number and disease severity [9,17,[27][28][29]. However, our results showed that phenotype cannot be predicted by the SMN2 copy number.…”
Section: Discussionsupporting
confidence: 92%
“…In our studied population, all patients with three SMN2 copies presented with milder types II and III phenotypes whereas all severe Type I carried two copies. Our data are in concordance with the reported inverse relationship between SMN2 copy number and disease severity [9,17,[27][28][29]. However, our results showed that phenotype cannot be predicted by the SMN2 copy number.…”
Section: Discussionsupporting
confidence: 92%
“…Several large studies have suggested that sex may have an influence on SMA phenotype [35,38]. Although the occurrence of SMA subtype was not stratified by sex in the Cure SMA sibling cohort, concordance and discordance rates in same-and different-sex sibships were not statistically significantly different.…”
Section: Discussionmentioning
confidence: 69%
“…A number of possible sources for variability in observed SMA phenotypes and general subtype concordance have been identified, including SMN2 copy number, aspects of motor function, sex, and birth order [34][35][36][37]. The severity of SMA is thought to be influenced by the amount of full-length SMN protein that is residually expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients lacking SMN1 but carrying higher SMN2 copy numbers or SMN2 mutations that lead to greater SMN production exhibit a milder phenotype. [8][9][10][11][12][13][14][15] Various mouse models that recapitulate different SMA severities display complex pathology manifested by the loss of lower motor neurons, defects in neuromuscular junctions, and abnormalities in peripheral tissues, including the heart, muscles, intestines, liver, and spleen. [16][17][18][19][20][21][22][23][24][25] Suggesting a gender-specific role of SMN, heterozygous mice producing low levels of SMN show incidences of male infertility.…”
Section: Introductionmentioning
confidence: 99%